2022
DOI: 10.3389/fbioe.2022.764237
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic Potency of Bone Marrow- and Adipose Tissue-Derived Mesenchymal Stem/Stromal Cells Results in Differing Vascular Network Phenotypes in a Microfluidic Chip

Abstract: The vasculature is an essential, physiological element in virtually all human tissues. Formation of perfusable vasculature is therefore crucial for reliable tissue modeling. Three-dimensional vascular networks can be formed through the co-culture of endothelial cells (ECs) with stromal cells embedded in hydrogel. Mesenchymal stem/stromal cells (MSCs) derived from bone marrow (BMSCs) and adipose tissue (ASCs) are an attractive choice as stromal cells due to their natural perivascular localization and ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
4
22
0
Order By: Relevance
“…However, in addition to indicating smooth muscle cell diferentiation and presence of smooth muscle cells, αSMA is expressed by myofbroblasts [111]. It may also indicate pericytic and proangiogenic functions of hASC [112].…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to indicating smooth muscle cell diferentiation and presence of smooth muscle cells, αSMA is expressed by myofbroblasts [111]. It may also indicate pericytic and proangiogenic functions of hASC [112].…”
Section: Discussionmentioning
confidence: 99%
“…Also, fibrin gel is used to support MVN formation in this study, consistent with its use in other self-organized perfusable MVNs formed in microfluidic devices. [78][79][80][81][82] Some studies, however, have used mixed matrices, such as fibrin/collagen and fibrin/matrigel mixture. Kim and colleagues were able to form perfusable MVNs in fibrin gel mixed with a low concentration of collagen I, [83] but others either failed [84] or found that pure fibrin gel scaffolds are preferable to collagen gel or collagen/fibrin combinations, because it significantly reduces matrix retractions during MVN maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In the physiological adult pattern, NG2/CSPG4 is present in multiple adult organ tissues [ 22 ]. For example, in regard to vascular mural progenitor cells, NG2/CSPG4 is expressed on heart cardiomyocytes in large vessels, specifically smooth muscle cells (SMAs) [ 44 ], and on PCs in the microvasculature [ 45 ], making it even more meaningful for heart disease [ 46 ] than it has been in studies on the CNS. Based on the vital lessons learned from studies showing that NG2/CSPG4 is expressed in the vasculature of other adult organs, such as the liver [ 23 , 47 ], pancreas [ 48 ], lungs [ 49 ], kidneys [ 7 ], eyes [ 50 ], skin [ 51 ], and bone marrow [ 52 ], it is possible that the blood vessel walls harbor a reserve of NG2/CSPG4-expressing PCs as progenitor cells that may be integral to the elusive origin of mesenchymal stem cells (MSCs) [ 36 , 52 , 53 ] and other related adult solid tissue stem cells (SSCs).…”
Section: Ng2/cspg4 As a Marker Of Precursor Or Progenitor Cells Outsi...mentioning
confidence: 99%